AB0439 Travelling with arthritis: a cross-sectional analysis of danish arthritis patients treated with biologics. (12th June 2018) - Szabados, F.; Rasmussen, C.; Linauskas, A.; Leutscher, P.; Kragh, J.
Abstract : Background: The development and introduction of biologics has rapidly revolutionised the therapeutic approach of chronic inflammatory diseases. Well-treated patients have high physical activity levels and long life expectancy. They travel widely for holiday, business or family visits. Biological drugs are administered either intravenously or subcutaneous and have to be kept cool. Objectives: To describe the travel patterns, the extent of pre-travel advice, travel insurance, vaccinations, adherence to biological treatment, and self-reported health related problems encountered by rheumatology patients in biologic treatment during their travel. Methods: A cross-sectional study was conducted in an out-patient clinic at the Department of Rheumatology, North Denmark Regional Hospital. During 2017 a questionnaire with focus on travel history was distributed to 300 consecutive arthritis patients treated with biologics. Results: A total of 273 (91%) completed the questionnaire. Median age was 67 years, and 53% were females. Overall 64% of them were receiving subcutaneous (sc) and 28% intravenous (iv) treatment, while in 8% administration route were not stated. Overall 15% of patients reported reduced travel activity after having started biologics and 21% reported that biological treatment or disease have directly influenced their decision about travelling. A total of 74% of patients have travelled outside of Denmark and 45% of these have travelled outside of Europe while treated with biologics. Pre-travel advice was sought by 26% and travel insurance was taken out by 86% of the travellers. However, 59% did not inform the insurance company about their disease or biologics. Only 6% of the travellers have experienced minor health problems which were not related to arthritis, while three patients were hospitalised. Overall 10% of patients were given additional travel vaccination. Patients, receiving sc biologics travelled significantly more than those, receiving iv treatment: 68% versus 21% (p<0.05). Overall 42% of the travellers in sc treatment group continued to take biologics during their travel, 21% had stopped the treatment before and 5% during the travel. A large proportion (72%) of travellers, who discontinued sc treatment prior to travelling, stopped the medication due to concerns about carrying biologics in general. Conclusions: Biological treated patients with rheumatic diseases travel frequently. Neither health-related problems nor treatments were reported to be major problems. The main problems were failure to seek pre-travel advice, worry for carrying biologics and the lack of disclosure regarding biologic treatment while seeking travel insurance. Patients receiving subcutaneous biological treatment travelled significantly more often than patients treated with intravenous biologics. References: [1] Dekkiche S, de Valliere S, D`Acremont V, Genton B. Travel related health risks in moderately and severally immunocompromised patients: a case-control study. J Travel Med2016:23. [2] Askling HH, Dalm VASH. The medically immunocompromised adult traveller and pre-travel counselling:status quo 2014. Travel Medicin and Infectious Disease2014:219–18. Disclosure of Interest: None declared